A review of blade tip clearance–measuring technologies for gas turbine engines. (March 2020) - Yu, Bing; Ke, Hongwei; Shen, Enyu; Zhang, Tianhong
Blade tip clearance is one of the important parameters affecting the performance, safety and stability of a gas turbine engine. However, it is difficult to measure the tip clearance in real time and accurately during the development and test process of an engine. In order to promote the development of tip clearance–measuring technology and the optimal design of the gas turbine engine, some typical measuring methods of tip clearance and a novel measuring method based on AC discharge are introduced. In this article, the significance for measuring tip clearance of an engine is illustrated first. Then, operating principles, characteristics and developments of those typical measurement approaches are introduced. After that, these methods are analyzed, and the particular characteristic of each measuring approach is summarized.